Temperature dependency of predation: Increased killing rates and prey mass consumption by predators with warming - Walker, Ryan (Ecol Evol, 2020)
Temperature dependency of consumer–resource interactions is fundamentally important for understanding and predicting the responses of food webs to climate change. Previous studies have shown temperature‐driven shifts in herbivore consumption rates and resource preference, but these effects remain poorly understood for predatory arthropods. Here, we investigate how predator killing rates, prey mass consumption, and macronutrient intake respond to increased temperatures using a laboratory and a field reciprocal transplant experiment. Ectothermic predators, wolf spiders (Pardosa sp.), in the lab experiment, were exposed to increased temperatures and different prey macronutrient content (high lipid/low protein and low lipid/high protein) to assess changes in their killing rates and nutritional demands. Additionally, we investigate prey mass and lipid consumption by spiders under contrasting temperatures, along an elevation gradient. We used a field reciprocal transplant experiment between low (420 masl; 26°C) and high (2,100 masl; 15°C) elevations in the Ecuadorian Andes, using wild populations of two common orb‐weaver spider species (Leucauge sp. and Cyclosa sp.) present along the elevation gradient. We found that killing rates of wolf spiders increased with warmer temperatures but were not significantly affected by prey macronutrient content, although spiders consumed significantly more lipids from lipid‐rich prey. The field reciprocal transplant experiment showed no consistent predator responses to changes in temperature along the elevational gradient. Transplanting Cyclosa sp. spiders to low‐ or high‐elevation sites did not affect their prey mass or lipid consumption rate, whereas Leucauge sp. individuals increased prey mass consumption when transplanted from the high to the low warm elevation. Our findings show that increases in temperature intensify predator killing rates, prey consumption, and lipid intake, but the responses to temperature vary between species, which may be a result of species‐specific differences in their hunting behavior and sensitivity to temperature.